Effect of workdays lost to presumptive malaria on food crop production in rural south west Nigeria (2019)
Malaria is a major public health problem in Nigeria, having negative effect on economic livelihood of farming households. Therefore, this study examined the effect of workdays lost to presumptive malaria on food crop production in rural South west Nigeria. A four-stage sampling technique was used to randomly select 395 food crop farming households from Oyo and Osun states based on probability proportionate to size. Structured questionnaire was employed in collecting primary data used in the study. Data were analysed using descriptive statistics and ordinary least square regression model at α0.05. Age of households’ head was 56.41±9.34 years. Male respondents were 88.6%, household size was 7±2 persons and 37.0% had no formal education. Only 45.1%, 24.6%, 37.2% and 7.1% had access to extension services, credit facilities, electricity and mosquito nets, respectively. In a year, the average number of presumptive malaria episodes per household was 17.49± 4.28. Workdays lost to malaria was 73.49±23.87, out of which 69.8% and 30.2% was due to sickness and caregiving, respectively. Household size (β=-1.00), hired labour (β=-0.25) and workdays lost to presumptive malaria (β=-0.12) reduced per capita food crop production while farm size (β= 0.42), fertilizer (β=0.43), herbicides used (β=0.15) and planting materials (β=0.11) increased per capita food crop production. Workdays lost to presumptive malaria had negative influence on household food crop production. Therefore, people in the study area should be encouraged to make proper use of malaria preventive measures, such as mosquito nets, so as to reduce frequency of mosquito bites and malaria attacks. Medication that can reduce the days of incapacitation should be intensified and made available to farmers at affordable prices in order to improve the quality of life and productivity of farming households. Also health education should form a core of educational and extension service delivery to the farmers especially in the rural areas where majority are into farming as means of livelihood.